Diamond encapsulated silicon optical fibers synthesized by chemical vapor deposition - Alex T. Hendrickson (AIP Advances, 2020)
Semiconductor optical fibers encapsulated in a protective diamond coating can theoretically lead to immense power handling capabilities and infrared functionality. Here, silicon optical fibers are grown using high pressure chemical vapor deposition before being coated by 50 μm–300 μm of diamond by microwave plasma-assisted chemical vapor deposition. This coating extends conformally around the fiber cross section with diamond crystallites in the film on the order of several micrometers. Complete coating of high-quality diamond around the fiber is indicated by scanning electron microscopy and Raman measurements. The encapsulated silicon fibers are durable enough to survive the diamond deposition process, as demonstrated by their ability to guide infrared light.